Doctors’ view about status of Teaching & Learning of Psychiatry at Undergraduate Medical Education in Bangladesh (Bangladesh Journal of Medical Education, 2021)
This descriptive type of cross-sectional study was carried out at different Upazilla levels hospitals of Dhaka, Chattogram, Khulna, Sylhet, Rajshahi, Barisal & Rangpur divisions. It was conducted to find out the views of the doctors serving at primary health care level about the status of teaching & learning of Psychiatry at undergraduate medical education level in Bangladesh. The contents, teaching-learning hours, teaching-learning methods & assessment needed for Psychiatry of undergraduate medical curriculum 2002 & 2012 of Bangladesh were also reviewed & compared by the researcher. The study period was July 2019 to June 2020. A self-administered semi-structured questionnaire with five-point Likert scale was used. Convenience sampling technique was adopted & total 307 doctors participated in this study with their valuable opinions. After reviewing and comparing of undergraduate curriculum 2002 & 2012, it was found that content coverage & 20 hours lecture in psychiatry was same in both curricula. But block posting was reduced from 5 days to 3 days & ward placements was reduced from 4 weeks to 3 weeks in the curriculum of 2012 from curriculum of 2002. In curriculum 2002, there were 17.5 marks in written and 01 OSCE station in practical for Psychiatry and one examiner from either Psychiatry or Dermatology in paper II of Medicine in final professional MBBS examination. But there is no such provision for psychiatry in curriculum 2012. Among 307 doctors, 287 (86.9%) agreed that behavioral science should be taught by Psychiatrist instead of Community Medicine Specialist. Only 36 (11.8%) respondents agreed that their learning & training in psychiatry were sufficient during MBBS. Although, 227 (73.9%) doctors agreed that in their practice, a major portion of the patients were suffering from psychiatric problem, only 84 (27.4%) of them were confident enough to manage common Psychiatric cases. Among respondents, 238 (77.6%) agreed that placement of MBBS students in psychiatry should be from 3rd year and 260 (84.7%) agreed that Psychiatry should be given more weightage in MBBS curriculum. Around 180 (58.4%) doctors agreed that Psychiatry should be a separate subject as per standard set by WFME. Regarding examinership, 69% (212) respondents agreed that there should be one examiner from psychiatry in MBBS final Professional examination and 86.9% (267) of the respondents agreed that the Psychiatric part of MBBS curriculum should be updated immediately. The study recommended to update the psychiatric portion of MBBS Curriculum considering psychiatry as a separate subject as per the directive of WFME & like many countries of the world.Bangladesh Journal of Medical Education Vol.12(2) July 2021: 18-22